2021
DOI: 10.3390/nu13061840
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Sex Differences in Rates and Correlates of Food Addiction Status in Women and Men with PTSD

Abstract: Background: Food addiction (FA) is a dysregulated eating pattern characterized by difficulties in controlling the intake of certain foods. There is an overlap in physical and mental health correlates of FA and post-traumatic stress disorder (PTSD). The purpose of this study was to examine sex differences in the rates of positive FA status in individuals with threshold/subthreshold PTSD, and to examine sex differences in the physical and mental health correlates of FA. Methods: Post-9/11 veterans/service member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Referring to our results, although e-learning burnout (an adverse direct effect of chronic online stress) illustrates similar educational difficulties and related maladaptive coping reaction -overeating, experienced by both, girls and boys, it may be more overwhelming to girls than boys because of presenting protective reactions in the forms of social isolation and withdrawal (lower interpersonal resources), and negative beliefs about self, lack of faith in control over the environment, loss of purpose in life goals and life meaning (poorer psychological well-being). Additionally, some researchers found no gender differences in a dysregulated eating pattern (food addiction), characterised by difficulties in controlling the intake of certain foods during the Covid-19 pandemic, which may be related to the level of post-traumatic stress disorder [64]. Our results support the above findings and suggest that girls are more vulnerable to e-school stress, which may indicate a higher level of overall stress caused by social isolation and physical distance.…”
Section: Note: S-students Stress; Oeb-overeating Behaviors; Esbs-elea...supporting
confidence: 84%
“…Referring to our results, although e-learning burnout (an adverse direct effect of chronic online stress) illustrates similar educational difficulties and related maladaptive coping reaction -overeating, experienced by both, girls and boys, it may be more overwhelming to girls than boys because of presenting protective reactions in the forms of social isolation and withdrawal (lower interpersonal resources), and negative beliefs about self, lack of faith in control over the environment, loss of purpose in life goals and life meaning (poorer psychological well-being). Additionally, some researchers found no gender differences in a dysregulated eating pattern (food addiction), characterised by difficulties in controlling the intake of certain foods during the Covid-19 pandemic, which may be related to the level of post-traumatic stress disorder [64]. Our results support the above findings and suggest that girls are more vulnerable to e-school stress, which may indicate a higher level of overall stress caused by social isolation and physical distance.…”
Section: Note: S-students Stress; Oeb-overeating Behaviors; Esbs-elea...supporting
confidence: 84%
“…According to previous studies, sex differences have been found in the prevalence of food addiction with mixed results ( Pedram et al, 2013 ; Stojek et al, 2021 ). In our study, more females met the “diagnosis” of food addiction as measured by the YFAS-F compared to males, but no sex differences were observed in terms of the food addiction symptom levels.…”
Section: Discussionmentioning
confidence: 92%
“…In primarily male veteran samples, current and lifetime diagnoses of PTSD were associated with FA symptoms [98,99]. In a clinical sample of men and women veterans, those with FA (18% of the overall sample) reported higher severity of PTSD and depression [100]. Overall, recent findings consistently indicate an overlap between experience of trauma and food addiction symptoms and suggest that men are as susceptible to FA in trauma-exposed samples as women (e.g., [98][99][100].…”
Section: Stress and Trauma As Environmental Factorsmentioning
confidence: 87%